Motorbike-Related Neurotrauma at a Neurosurgical Unit - Munema Khan, Muhammad Motism Shah, Yasir Shahzad, Maryam Khan (Journal of Rawalpindi Medical College, 2018)
Background :. To analyze patterns of motorbike-related neurotrauma and to decipher where the current scenario can be best optimized. Methods : In this descriptive, prospective, cross-sectional study, cases of motorcycle-accidents with neurotraumatic injuries were included .Variables noted were age, mode of presentation, gender, type of head-injury, associated injury,outcome,type of rider, socioeconomic status, helmet-use, education-level, residence, mode of treatment, duration of hospitalization and permanent-disability. All patients were treated for their respective injuries and complications and were managed as per standard protocols. Results : In 100 patients predominant age group was 14-29 years. Worse outcome was seen in rural residents and first-riders. Bleeds outnumbered fractures and concomitant orthopedic injuries were the most common associated injury. Helmet use rate of only 8% and an expiry rate of 11% along with permanent disability in 3 patients was noted. The significantly higher fatality rate was seen in sub-dural-hematomas. Conclusion: Road traffic accident (RTA)-Associated neurotrauma is a pressing problem in young males and the high disability and injury rate can be accounted to non-compliance with helmet-use and ignorance of road-safety. The worse outcome is associated with subdural-haematomas (SDH), first-riders, referred-cases, and rural residence. Effective legislation and collective community effort is needed to counter the dilemma.